Design of a wideband strip helical antenna for 5G applications - Mohammed Yousif Zeain; M. Abu; Z. Zakaria; Ahmed Jamal Abdullah Al-Gburi; R. Syahputri; A. Toding; Sriyanto Sriyanto (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents the design of wideband strip helical antenna for 5G application. The strip helical antenna is designed for 5G and wideband applications that provide a wide bandwidth and circular polarization. The helical antenna is planned on at 5.8 GHz frequency by using teflon material. The new designed strip is printed on a substrate then rolled into a helix shape to achieve circular polarization without an impedance matching and that the proposed antenna can be used for potential applications in wideband wireless communication. A wideband bandwidth of 2.41 GHz with a resonant frequency at 5.8 GHz is achieved by the helical antenna on the teflon substrate. The presented antenna on teflon substrate has achieved a gain of 11.2 dB. The antenna design parameters and the simulated results are achieved using the commercial software CST. The proposed antenna can be used for various wireless applications such as wideband, ultra wideband, 5G and wireless applications.